Making Interdisciplinary Collaboration Work: Key Ideas, a Case Study and Lessons Learned - McMurtry, Angus; Clarkin, Chantalle; Bangou, Francis; Duplàa, Emmanuel; MacDonald, Colla; Ng-A-Fook, Nicholas; Trumpower, David (Alberta Journal of Educational Research, 2012)
This article discusses the ‘lessons learned’ from an attempt to establish an interdisciplinary education research group. The growth, development and dissolution of the group are treated as an instrumental case study. Current literature on interdisciplinary collaboration is synthesized in order to provide a frame for analysis. Data was collected over several years and included three rounds of written participant reflections and documentation of group activities and meetings. Five major themes arose from the research, covering issues such as disciplinary diversity, common ground, interpersonal relationships, career pressures, and the need for concrete problems and tangible progress. Based on these themes, a number of ‘lessons learned’ are discussed which will likely be of great interest to those considering similar interdisciplinary initiatives. Cet article discute des «leçons apprises» d’une tentative visant l’établissement d’un groupe de recherche sur l’enseignement interdisciplinaire. La croissance, le développement et la dissolution du groupe sont présentés comme une étude de cas déterminante. Les ouvrages actuels portant sur la collaboration interdisciplinaire sont synthétisés de sorte à produire un cadre pour l’analyse. La collecte des données s’est étendue sur plusieurs années et a impliqué trois cycles de réflexions écrites par les participants et de documentation des activités de groupe et des réunions. Cinq grands thèmes ont découlé de la recherche, portant sur des questions comme la diversité disciplinaire, le terrain d’entente, les relations interpersonnelles, les pressions professionnelles, et le besoin de problèmes concrets et de progrès tangibles. À partir de ces thèmes, on discute de plusieurs «leçons apprises» qui intéresseront sans doute ceux qui envisagent des initiatives interdisciplinaires similaires.